PENGARUH SENAM OTAK (BRAIN GYM) TERHADAP TINGKAT STRES MAHASISWA (STUDI DILAKUKAN PADA MAHASISWA SEMESTER 8 PRODI KEPERAWATAN STIKES WIRA MEDIKA BALI): EFFECTS OF BRAIN GYM AGAINST STUDENT STRESS LEVELS (STUDY CONDUCTED ON 8TH SEMESTER STUDENTS OF NURSING STUDY PROGRAM STIKES WIRA MEDIKA BALI) - Purwanti, Ika; Marantika, M Andre; Adilatri, A.A Sri Agung (Stikes Wira Medika Bali, 2019)
During the process of preparing the thesis students are challenged and trained to carry out a series of scientific activities that test a theory and solve a problems with a critical mindset (critical thinking).Student stress in compiling a thesis due to difficulty in finding references and deadline task pressure . One of therapy to decreasing stress level is brain gym therapy. The aimed of this study was to determine the effect of brain gym on college student stress level. This study was used pra-experiment method with one group pre-test – post-test design. The number of samples in this study obtained 66 peoples with simple random sampling techniques. The research was conducted at Stikes Wira Medika Bali. Stress levels were measured by the DASS 42 questionnaire. The results showed that the stress levels of students before being given brain gym were 43 people with moderate stress level category and student stress levels after being given brain gym therapy with 50 people with light stress levels. The results of the Wilcoxon Signed Rank Test statistical test with a significance level of 0.05 indicate the value of p=0.000<0.05. This study concludes that there is an effect of brain gymnastic on student stress level. Based on the results of this study, it is recommended for the college student who is experiencing stress during writing their thesis could use brain gym for reducing stress level.